PENGGUNAAN STRATEGI PEMBELAJARAN PEER LESSON UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan Kelas di Kelas X MIA 7 SMA Negeri 2 Cimahi) - Citra Maharani; Yani Kusmarni; Yeni Kurniawati (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This research aims to improve students’ interpersonal intelligence by using peer lesson learning strategy. This research is based on the findings of learning conditions in the classroom which shows the students’ interpersonal intelligence is still low. Low interpersonal intelligence of students can be seen from the way students cooperation and how to convey opinions to other students. The formulation of research problem in this research is how to plan peer lesson learning strategy, how the implementation stages of peer lesson learning strategy, how to improve interpersonal intelligence after using peer lesson strategy and teacher’s effort in overcoming obstacles by using peer lesson learning strategy to improve intelligence interpersonal students. Thus, the researcher did a research by using Classroom Action Research Methods by adopting Kemmiss and Taggart models. The design of this model has several stages: action planning, action execution, observation, and reflection for revision in the next action. Data collection techniqs used observation, interviews and documentation studies. Meanwhile, data collection tools used interview guides, observation guides and field notes. Based on the result of the research showed an increasement of students’ interpersonal intelligence in history learning by using peer lesson learning strategy. The increasement can be seen from the achievement of several indicators of improvement of students’ interpersonal intelligence, among others; teach peers, engage in group or joint activities, work effectively with others and communicate effectively, both verbally and non-verbally. Based on the results of research, by using peer lesson learning strategy can be a solution to improve students’ interpersonal intelligence in learning history in class X MIA 7 SMA Negeri 2 Cimahi.